Third International Symposium on 3D Data Processing, Visualization, and Transmission (3DPVT'06) 2006
DOI: 10.1109/3dpvt.2006.38
|View full text |Cite
|
Sign up to set email alerts
|

Building a 3D Virtual Museum of Native American Baskets

Abstract: In this paper we report our progress in building a system for the acquisition, analysis, and visualization of a collection of Native Californian baskets from the Phoebe A. Hearst Museum of Anthropology. Our project differs from existing cultural heritage applications in terms of its focus: to build tools and techniques for visualizing and studying a large number of related objects -in this case, baskets. We present our progress in the following system components: (i) laser-scanning of baskets, (ii) constructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…This research differs from existing cultural heritage applications in terms of the focus on tools and techniques to display objects, and to study the related ones. In the case of the basket, researchers developed a model in 3D, and exhibits in virtual view [6].…”
Section: Related Workmentioning
confidence: 99%
“…This research differs from existing cultural heritage applications in terms of the focus on tools and techniques to display objects, and to study the related ones. In the case of the basket, researchers developed a model in 3D, and exhibits in virtual view [6].…”
Section: Related Workmentioning
confidence: 99%
“…VolkanIsler and et al [3] have created a system for the analysis and display of a collection of Native Californian baskets of Phoebe A. Hearst Museum of Anthropology. This research differs from existing cultural heritage applications in terms of the focus on tools and techniques to display objects, and to study the related ones.…”
Section: Related Workmentioning
confidence: 99%
“…Khainaga [2] built a museum presentation about Thai architecture: case study Thai Lue houses, and studied the effectiveness of learning in virtual presentation. The study found that following the virtual media museum of Thai Lue houses, the understanding of students.VolkanIsler and et al [3] have created a system for the analysis and display of a collection of Native Californian baskets of Phoebe A. Hearst Museum of Anthropology. This research differs from existing cultural heritage applications in terms of the focus on tools and techniques to display objects, and to study the related ones.…”
mentioning
confidence: 99%
“…Patel et al [29] presented a system designed to create 3D virtual exhibitions of museum artifacts. Isler et al [30] described a similar system focused on 3D digital replicas of Native American baskets. Recently, Fominykh et al [31] presented a 3D virtual museum which incorporates collaborative technologies in order to serve as a virtual workshop for educational purposes.…”
Section: Web-based 3d Environmentsmentioning
confidence: 99%